Penguatan Strategi Marketing Umkm D&D Handycraft Melalui Branding Produk Dan Design Di Wilayah Sentul, Kota Blitar - Putri Kurniawati; Ririt Iriani Sri S; Mohammad Wahed (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In developing Micro, Small, and Medium Enterprises (MSMEs) it is necessary to have a strategy in marketing its products that aims to increase competitiveness and increase in business development, one of which is through branding so that it has its own distinctive characteristics when compared to MSMEs whose businesses are the same and can also be recognized wider by society. This service aims to provide reinforcement to the community's creative industries (MSMEs) in the Sentul area, Kepanjenkidul District, Blitar City regarding marketing strategies through product branding and design. The methods used in this service activity are direct presentations, discussions, and mentoring. Strengthening this marketing strategy was carried out for three days which coincided at the D&D Handycraft UMKM Shop which was witnessed by the shop owner. For the smooth running of this community service activity, the East Java